Selected Abstracts of the 2nd Congress of joint European Neonatal Societies (jENS 2017); Venice (Italy); October 31-November 4, 2017; Session "Neonatal Gastrointestinal Physiology and NEC" - - (Hygeia Press di Corridori Marinella, 2017)
Selected Abstracts of the 2nd Congress of joint European Neonatal Societies (jENS 2017); Venice (Italy); October 31-November 4, 2017 58th ESPR Annual Meeting, 7th International Congress of UENPS, 3rd International Congress of EFCNI ORGANIZING INSTITUTIONS European Society for Paediatric Research (ESPR), European Society for Neonatology (ESN), Union of European Neonatal & Perinatal Societies (UENPS), European Foundation for the Care of Newborn Infants (EFCNI) ORGANIZING COMMITTEE Luc Zimmermann (President of ESPR), Morten Breindahl (President of ESN), Manuel Sánchez Luna (President of UENPS), Silke Mader (Chairwoman of the Executive Board and Co-Founder of EFCNI) SCIENTIFIC COMMITTEE Virgilio P. Carnielli (Congress President Chair), Pierre Gressens (Past Scientific President), Umberto Simeoni, Manon Benders, Neil Marlow, Ola D. Saugstad, Petra Hüppi, Agnes van den Hoogen Session "Neonatal Gastrointestinal Physiology and NEC" ABS 1. DETRIMENTAL MUCOSAL EFFECT OF IBUPROFEN IN THE IMMATURE HUMAN INTESTINE • E. Tremblay, E. Ferretti, M.-P. Thibault, D. Grynspan, K.M. Burghardt, M. Bettolli, C. Babakissa, E. Levy, J.-F. Beaulieu; Research Consortium on Child Intestinal Inflammation ABS 2. CORRELATION BETWEEN CALPROTECTIN LEVELS IN MECONIUM AND VITAMIN D STATUS IN CORD BLOOD: ASSOCIATION WITH INTESTINAL DISTRESS DURING NEONATAL PERIOD • S.H. Park, W.H. Kim, Y.M. Lee ABS 3. COMPARISON OF FECAL CALPROTECTIN LEVELS ACCORDING TO FEEDING KINDS IN VERY PRETERM INFANTS • J.H. Park, N.H. Lee, S.Y. Shin, C.S. Kim, S.L. Lee, W.M. Lee ABS 4. NEONATAL MORBIDITY OF EXTREME PRETERM INFANTS BEFORE AND AFTER THE INTRODUCTION OF A DONOR HUMAN MILK BANK AT THE PERINATAL CENTER GROßHADERN • V. Lieftüchter, M. Kujawa, A. Schuze, A.W. Flemmer, S. Herber-Jonat ABS 5. IS NEAR INFRARED SPECTROSCOPY A RELIABLE TECHNIQUE TO MEASURE GUT PERFUSION IN PRETERM INFANTS? • J. Banerjee, T.S. Leung, N. Aladangady ABS 6. EARLY BIOCHEMICAL MARKERS ASSOCIATED WITH DEVELOPMENT OF NECROTIZING ENTEROCOLITIS • K.W. Olsson, R. Sindelar ABS 7. OPTICAL PROPERTIES OF EARLY STOOL FROM PRETERM INFANTS: IMPORTANT TO CONSIDER FOR ABDOMINAL OXIMETRY BASED ON NEAR-INFRARED SPECTROSCOPY • H. Isler, D. Schenk, J. Bernhard, F. Scholkmann, S. Kleiser, D. Ostojic, D. Bassler, M. Wolf, T. Karen ABS 8. STOOLING PATTERN AND GASTRIC RESIDUALS ARE NOT USEFUL TOOLS FOR EARLY DIAGNOSIS OF NECROTISING ENTEROCOLITIS IN PRETERM INFANTS • S. Carlsson, M. Domellöf, A. Elfvin ABS 9. REFERENCE VALUES OF ZONULIN IN TERM NEONATES • A. Tarko, A. Suchojad, A. Jarosz-Lesz, M. Majcherczyk, M. Michalec, I. Maruniak-Chudek ABS 10. DETERMINANTS OF THE NEED FOR TREATMENT IN PREMATURE INFANTS WITH SUSPECTED NECROTISING ENTEROCOLITIS • N. Bussmann, A. El-Khuffash, D. Corcoran ABS 11. EFFECT OF ANTIBIOTIC PROPHYLAXIS DURING REMOVAL OF A CENTRAL VENOUS CATHETER ON DEVELOPMENT OF THE NEONATAL INTESTINAL MICROBIOTA • E. d'Haens, R. Zwittink, C. Belzer, M. Hemels, R. van Lingen, I. Renes, J. Knol, D. van Zoeren-Grobben ABS 12. NEWBORNS WITH ULTRASOUND FINDING OF GAS IN HEPATIC PORTAL VENOUS SYSTEM: ANALYSIS OF RISK FACTORS, CLINICAL AND LABORATORY FINDINGS AND DEVELOPMENT OF ALLERGY • J. Lozar Krivec, A. Nyasha Zimani, N. Zupančič, D. Paro-Panjan ABS 13. NEONATAL FECAL BIOMARKERS OF NECROTIZING ENTEROCOLITIS • I. Tofé, M.V. Rodriguez-Benitez, C. Hernandez-Chirlaque, M. Gil-Campos, M.D. Ruiz-Gonzalez, A. Martinez ABS 14. THE OPEN ABDOMEN: A CHALLENGE FOR NEONATOLOGISTS AND NEONATAL SURGEONS. THE KAROLINSKA EXPERIENCE • M. Bartocci, E. Palleri, A. Svenningsson, T. Wester ABS 15. ANOGENITAL STIMULATION IN RATS DOES NOT INCREASE GASTRIC EMPTYING • C.H. Ferreira, J. Belik ABS 16. THE PRETERM INFANT GASTRIC EMPTYING RATE IS DEPENDENT ON THE FEED VOLUME AND NOT ON POSTNATAL AGE • C.H. Ferreira, F.E. Martinez, G.C. Crott, J. Belik ABS 17. NECROTIZING ENTEROCOLITIS IN A NEONATAL INTENSIVE CARE UNIT • M. Branco, I. Falcão, T. Lopes, E. Proença, A. Almeida, C. Carvalho, L. Pinho ABS 18. SPONTANEOUS INTESTINAL PERFORATION: A DIAGNOSTIC CHALLENGE IN THE NEWBORN • M. Branco, T. Lopes, I. Falcão, L. Pinho, C. Enes, A. Almeida, C. Carvalho, E. Proença ABS 19. OUTCOMES OF EXTREMELY LOW BIRTH WEIGHT BABIES RECEIVING SURGICAL TREATMENT FOR NECROTISING ENTEROCOLITIS • J. Ashton, C. Charlesworth, P. Yajamanyam ABS 20. ASSESSMENT OF ENZYMOTHERAPY EFFICACY IN CASE OF LACTASE INSUFFICIENCY IN PRETERM INFANTS • O. Vlasova, L. Koliubakina ABS 21. THE NORWEGIAN PRETERM INFANT GUT (PINGU) STUDY: A METAGENOMIC APPROACH TO GUT MICROBIOTA COMPOSITION AND RESISTOME IN INFANTS SUPPLEMENTED WITH PROBIOTICS • E. Esaiassen, E. Hjerde, P. Cavanagh, T. Pedersen, J. Andresen, S. Rettedal, R. Støen, B. Nakstad, N.P. Willassen, C. Klingenberg ABS 22. NECROTIZING ENTEROCOLITIS: WHAT ASPECTS IN 2017? • H. Ben Salem, I. Kasraoui, M.T. Lamouchi, E.D. Bouaicha, N. Kasdallah, S. Blibech, M. Doagi ABS 23. ROUTINE PROBIOTICS FOR PRETERM NEONATES: EXPERIENCE IN A TERTIARY AUSTRALIAN NEONATAL INTENSIVE CARE UNIT • G. Deshpande, V. Shingde, L. Downe, J. Xiao, M. Taber ABS 24. MATERNAL RISK FACTORS FOR NEC IN PREMATURES INFANTS WITH GA UNDER 28 WEEKS • L. Olariu, G. Olariu, S. Olariu